THE LOVE STORY OF BARIDIN AND RATMINAH FROM THE LAND OF CIREBON IN A WEBTOON COMIC ILLUSTRATION (Arty: Jurnal Seni Rupa, 2021)
The Webtoon comic "The Love Story of Baridin and Ratminah” was created with the aim of applying the skills of writers during their college years in the Fine Arts department, and was also made to preserve Cirebon's regional culture, namely the performance arts of Tarling Baridin and Ratminah, which are now becoming rare. This work was created as a promotional medium for House Of Imagi Studio, as a comic studio. The process of creating the Webtoon comic "The Love Story of Baridin and Ratminah" is carried out in 4 stages, namely, preliminary plans (finding ideas, collecting data, analyzing target audiences, determining the concept of the work, and selecting materials), pre-production (designing comic assets, designing characters, designing background, text selection, storyboard design, word balloon selection), production (the process of making illustrations, editing comics, composing comics, consulting with lecturer, consulting with clients), and post-production (designing supporting media, pre-exhibition). The design of the Webtoon comic book "The Love Story of Baridin and Ratminah" has produced 3 works, 1 main work and 2 supporting works. The Webtoon comic “The Love Story of Baridin and Ratminah” includes a message style theory, visual language, art principles, and visual figures.